Internet marketing strategy forfurniture industry: a research based ergonomics sofa - Suriatini Ismail; Anis Amira Abdul Rahman; Ahmad Rasdan Ismail; Khairul Azhar Mat Daud; Nik Zulkarnaen Khidzir (2017)
The objective of this paper is to reveal the awareness of ergonomics as part of internet based marketing strategy in furniture industry. Based on Actor Network Theory (ANT), this study believes that internet marketing is an object that links buyer and seller. Empirical study of previous practices has failed to indicate common use of ergonomics term in this research area of marketing strategy. Most of the marketing strategy literature in furniture industry has focused more on aesthetic than ergonomics issues. Therefore, this study utilized qualitative research to analyze the use of ergonomics term in the websites for marketing strategy. This study has identified 33 websites of furniture industry to address the issues using purposive sampling technique and content analysis. The finding shows the ergonomics term is not a common exposure in the websites of furniture industry. It confirms the lack of awareness about the utilization of ergonomics term in the companies’ websites. This research recommends that future marketing strategy should highlight the ergonomics issues in the company’s website in order to promote public health. Hence, this new knowledge suggests that the furniture industry should be more health conscious. Furthermore, future research can also focus on other tools of digital marketing strategy.